'As Long as I Can Do, I Will Do for Children': Sindiwe Magona's Children's Literature. (July 2020) - Schatteman, Renée
Abstract : Sindiwe Magona is a celebrated South African writer for children. Her books have appeared in both English and Xhosa and are widely prescribed and used in schools. This short essay on Magona and her works is followed by an interview conducted with her in 2019.